Development of a critical thinking skills instrument through problem-based learning for senior high school students - Dimas Iqbal; Mustaji Mustaji; Lamijan Hadi Susarno (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
This study aims to develop an assessment instrument, comprising essay questions and scoring rubrics, to measure high school students’ critical thinking skills through Problem-Based Learning (PBL). The instrument was developed by adapting the Research and Development (R&D) design using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Expert validation results indicated that the instrument was suitable for use, with minor editorial revisions recommended to improve clarity and objectivity. A trial conducted with 67 students showed that all assessment items were valid (r-calculated > r-table) and the instrument demonstrated high reliability (Cronbach’s Alpha = 0.745). The scoring rubric consists of six main indicators referring to the critical thinking framework by Robert Ennis (1993): focus, supporting reasons, reasoning, organisation, language use, and relevance. This instrument is considered effective in supporting authentic assessment and can be used by teachers to evaluate students’ critical thinking skills more systematically, in line with the Merdeka Curriculum and 21st-century competency demands.